(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This is a review of a book entitled (Drawing and Poetry: Commonalities of Life and Action) written by the artist and poet Hashim Tayeh. The researcher sought to review, summarize, and present an idea about it, after introducing its author. Hashim Tayeh, a visual artist, was born in Basra in 1948. He obtained a BA in Arabic Language and Literature in 1970. He practiced painting and held solo exhibitions in Basra during the years: 1974, 1976, and 1989, and an art exhibition in 1992 in the hall of the Iraqi National Museum in Baghdad. He also practices photography and published his photos with his dazzling commentaries in the semi-weekly newspaper “Al-Manara”, which was issued in Basra. Hashim Tayeh also writes poetry. His first poetry collection “The Cart of the Day” was published with the support of the Asia Cell Communications Company. He also writes short stories and won first prize in a competition held by the Iraqi newspaper “Al-Mu’tamar”. He also writes art criticism. The artist Hashem Tayeh also held his sculpture exhibition entitled (Exiles) in the hall of the Cultural House in Basra, which included (24) sculptures, relying on unconventional materials and materials used in daily life. The book "Drawing and Poetry (Commonalities of Life and Action)" by Hashem Tayeh explores the relationship between the arts, especially drawing and poetry, by analyzing the commonalities between them. The book focuses on how each art influences the other and how they can interact to produce innovative works of art. The book is an attempt to revisit a number of actors and forces that have invested vitally in the two most ancient human arts: painting and poetry, and produced, through their presence in their expressive representations, an example of lively interaction between texts, and a possibility for dialogue, cross-pollination, and the exchange of influences and energies on common ground, and in a free creative space that operates with an open expressive mood, and develops its material with high flexibility, to finally allow for the settlement of a comprehensive level suitable for cultivating hybrid textual effects, the fruits of which can be reaped through grafting of their original constituent components with components of other effects. The responses of texts to each other, and their association with others, represent a response to their internal seductive tendency to rest a little, or a lot, from the constraints of their essences that determine them and their uniqueness, and they are, without a doubt, a response to the human imagination that does not settle on a state, the playful imagination that is never free from its passion for crafting surprising artistic mixtures from the wonders of various materials. The interactions, penetrations, and fusions of artistic effects reflect the harmony that pervades the world, whose living beings and phenomena are strengthened by each other, and in which every being is organized through indispensable relationships with other beings. In ancient and modern times, painting has been defined by poetry, and poetry by painting, based on the forces and agents by which they produced their two effects. This book of ours does not stray far from its design to discover the commonalities in life and action between painting and poetry.